IEEE Symposium Conference Record Nuclear Science 2004.
DOI: 10.1109/nssmic.2004.1462205
|View full text |Cite
|
Sign up to set email alerts
|

Source-search sensitivity of a large-area, coded-aperture, gamma-ray imager

Abstract: We have recently completed a large-area, codedaperture, gamma-ray imager for use in searching for radiation sources. The instrument was constructed to verify that weak point sources can be detected at considerable distances if one uses imaging to overcome fluctuations in the natural background. The instrument uses a rank-19, one-dimensional coded aperture to cast shadow patterns onto a 0.57 m 2 NaI(Tl) detector composed of 57 individual cubes each 10 cm on a side. These are arranged in a 19 x 3 array. The mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…One technique that has proven effective in overcoming this limitation is the use of radiation imaging to "see through" this background clutter [4], [5]. In a proof-ofprinciple (POP) instrument, we have successfully demonstrated the detection of a 1-mCi Cs source at a range m [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One technique that has proven effective in overcoming this limitation is the use of radiation imaging to "see through" this background clutter [4], [5]. In a proof-ofprinciple (POP) instrument, we have successfully demonstrated the detection of a 1-mCi Cs source at a range m [4].…”
Section: Introductionmentioning
confidence: 99%
“…One technique that has proven effective in overcoming this limitation is the use of radiation imaging to "see through" this background clutter [4], [5]. In a proof-ofprinciple (POP) instrument, we have successfully demonstrated the detection of a 1-mCi Cs source at a range m [4]. Further, by demonstrating that the background variation in the imaged data is normally distributed, we have shown that the size of the detector can be made arbitrarily large with a commensurate increase in sensitivity proportional to the square root of the detector area [4].…”
Section: Introductionmentioning
confidence: 99%
“…Each pinhole produces its own image at the detector plane, with the images from the different pin-holes being shifted with respect to one another. Mathematical processing techniques, such as spatial deconvolution, are used to generate a single image from the multiple overlapping images [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Encounters with discrete radioactive sources generally exhibit rapid temporal variation and are well described using point-source models. Ziock et al exploited this attribute in developing a coded-aperture imaging device for source search while Runkle et al developed point-source detection algorithms for radiation portal monitors [3], [4]. The TES concept exploits this discriminatory feature by passively inducing a signature specific to point-sized sources that is relatively immune to distributed sources.…”
Section: Introductionmentioning
confidence: 99%